1983
DOI: 10.1126/science.6828859
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface-Active Phospholipids in Gastric Cytoprotection

Abstract: Intragastric administration of a liposomal surfactant suspension markedly reduced acid-induced gastric ulcerogenesis and bleeding in rats. The concentration of surface-active molecules intrinsically present in the gastric mucosa was increased two to six times by administration of 16,16-dimethyl prostaglandin E2. Thus, local accumulation of surface-active phospholipids may be an integral component of the cytoprotective mechanism activated by prostaglandin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
1
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(108 citation statements)
references
References 27 publications
1
104
1
2
Order By: Relevance
“…nism (20)(21)(22), but these effects are not without controversy (23,24). Mersereau and Hinchey (25) proposed that dissolution of the mucosal folds may be associated with the prevention of necrotic gastric lesions along the fold crests in the stomach after exposure to necrotizing agents.…”
Section: Discussionmentioning
confidence: 99%
“…nism (20)(21)(22), but these effects are not without controversy (23,24). Mersereau and Hinchey (25) proposed that dissolution of the mucosal folds may be associated with the prevention of necrotic gastric lesions along the fold crests in the stomach after exposure to necrotizing agents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, association of NSAIDs with phospholipids has been suggested to improve GI safety of these drugs (3). The presence of an adsorbed layer of surface-active phospholipids on the surface of the mucus that covers the surface epithelium is suggested to protect the GI tissues by providing a hydrophobic layer between the epithelium and the luminal contents (4,5). It has been reported that NSAIDs associated with zwitterionic phospholipids may reduce GI toxicity (3).…”
mentioning
confidence: 99%
“…Submicron emulsions as a novel system to reduce the hemolytic effect, its mechanism of the protective effect was reported as follows: The first theory by Lichtenberger et al 25) suggested that phospholipids protect membranes by being adsorbed as a monolayer onto the surface, thereby creating a hydrophobic barrier which results in a reduction of hemolysis. The second theory by Martin et al 26,27) correlated this behavior to the protective function of phospholipids themselves, as they were able to form mixed micelles with the other molecules as a complex.…”
Section: In Vivomentioning
confidence: 99%